2020
DOI: 10.1111/gcb.15102
|View full text |Cite
|
Sign up to set email alerts
|

Low‐severity fire as a mechanism of organic matter protection in global peatlands: Thermal alteration slows decomposition

Abstract: Worldwide, regularly recurring wildfires shape many peatland ecosystems to the extent that fire‐adapted species often dominate plant communities, suggesting that wildfire is an integral part of peatland ecology rather than an anomaly. The most destructive blazes are smoldering fires that are usually initiated in periods of drought and can combust entire peatland carbon stores. However, peatland wildfires more typically occur as low‐severity surface burns that arise in the dormant season when vegetation is desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 136 publications
(283 reference statements)
1
37
0
Order By: Relevance
“…Turetsky, Donahue, and Benscoter (2011) reported that after long-term experimental drainage, combustion carbon losses during wildfire became ninefold higher in a boreal peatland, even though the carbon accumulation rates have doubled. Low-severity fire modifies the chemistry of soil organic matter and further, stabilizes C storage in peatlands from all regions (Flanagan et al 2020), but these positive effects may be weakened with increased fire severity after drainage or drought. Indirect effects of water table alteration through wildfire are overlooked and therefore, need to be incorporated in future research.…”
Section: Effects Of Water Level Alteration On Carbon Balancementioning
confidence: 99%
“…Turetsky, Donahue, and Benscoter (2011) reported that after long-term experimental drainage, combustion carbon losses during wildfire became ninefold higher in a boreal peatland, even though the carbon accumulation rates have doubled. Low-severity fire modifies the chemistry of soil organic matter and further, stabilizes C storage in peatlands from all regions (Flanagan et al 2020), but these positive effects may be weakened with increased fire severity after drainage or drought. Indirect effects of water table alteration through wildfire are overlooked and therefore, need to be incorporated in future research.…”
Section: Effects Of Water Level Alteration On Carbon Balancementioning
confidence: 99%
“…Finally, the recent criticism of two studies, Heinemeyer et al (2018) and Marrs et al (2019a), showing considerable C accumulation under rotational burning, was based on a model by Young et al (2019), which remains non-validated, unspecified, irrelevant (only deep drainage and not burning impacts), and omits key C storage aspects via charcoal (see pre-print responses by and Heinemeyer et al (2021)). In fact, recent studies by Leifeld et al (2018) and Flanagan et al (2020) support the findings of Heinemeyer et al (2018) and Marrs et al (2019a) that low-severity (i.e. prescribed) fires can result in high soil C accumulation rates in peatlands.…”
Section: Methodological Issues: Correlative Studies Vs Controlled Experimental and Model Assessmentsmentioning
confidence: 63%
“…Indeed, Young et al's criticism of two recent burning studies [2,3] is based on nonvalidated and unexplained model scenarios that omit crucial fire-mediated C cycle processes; we urge peatland researchers to include such burn-related C-cycle processes within future model scenarios [2,7] . For example, (i) net C fluxes at the three Heinemeyer et al sites [2] (see the Peatland-ES-UK website [12] ) indicate a potentially high net C uptake on regrowing burnt plots (possibly higher than that of unburnt plots with aging/degenerating heather and soon to offset combustion losses, but this requires a complete burn rotation to allow comparing cumulative C flux budgets versus C stocks estimates); (ii) recent work [14] adds to the prescribed heather burning work [2,3] in highlighting the positive role that charcoal (produced during cool burns or low-severity fires) can have on peatland C storage (e.g. it has the potential to increase peat C stocks by adding recalcitrant Corg in the form of charcoal and further reducing C losses via decomposition of soil organic matter); finally, (iii) a recent study suggests that low-severity fires may reduce methane emissions relative to no burning or high-severity fires in cooler climates [15] .…”
Section: Discussionmentioning
confidence: 99%